2018
DOI: 10.1016/j.appet.2017.11.084
|View full text |Cite
|
Sign up to set email alerts
|

Family meals then and now: A qualitative investigation of intergenerational transmission of family meal practices in a racially/ethnically diverse and immigrant population

Abstract: Having frequent family meals has consistently been associated with better health outcomes in children/adolescents. It is important to identify how intergenerational transmission of family meal practices occurs to help families benefit from the protective nature of family meals. Limited studies exist that explore the intergenerational transmission of family meal practices, particularly among racially/ethnically diverse and immigrant populations. This study explores how parents describe differences and similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…For example, prior studies have indicated the importance of having rules at family meals (e.g., electronics, flexible scheduling so family members can be at family meals) and that a positive emotional atmosphere at family meals is associated with child healthy weight and weight-related behaviors, which was also identified in the qualitative findings in the current study. 19,23,[27][28][29] One result from the current study that extends past findings includes the qualitative theme regarding having more breakfast and lunch family meals on weekend days versus weekdays. One hypothesis for this finding is that families may have more time on the weekends to carry out these different family meal types and may find them more reinforcing because they are less rushed, or include more home-cooked foods, which potentially leads to having more breakfast and lunch family meals on the weekend.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For example, prior studies have indicated the importance of having rules at family meals (e.g., electronics, flexible scheduling so family members can be at family meals) and that a positive emotional atmosphere at family meals is associated with child healthy weight and weight-related behaviors, which was also identified in the qualitative findings in the current study. 19,23,[27][28][29] One result from the current study that extends past findings includes the qualitative theme regarding having more breakfast and lunch family meals on weekend days versus weekdays. One hypothesis for this finding is that families may have more time on the weekends to carry out these different family meal types and may find them more reinforcing because they are less rushed, or include more home-cooked foods, which potentially leads to having more breakfast and lunch family meals on the weekend.…”
Section: Discussionsupporting
confidence: 75%
“…There has also been some prior qualitative research conducted with parents to identify meal characteristics of importance for promoting family meal frequency. 19,[27][28][29] These studies have provided a solid first step in understanding key meal characteristics (e.g., rules at meals, importance of family meals) 19,[27][28][29] from a parent's perspective that may increase the likelihood of family meals occurring. A next important step is to utilize mixed methods to provide both depth (qualitative) and breadth (quantitative) in understanding meal characteristics associated with family meal frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from our mixed-methods study support and extend prior quantitative work on intergenerational transmission of family meals ( 31 33 , 35 ) by providing rich, detailed information on factors that distinguish how different family meal patterns are passed between generations. That said, it should be noted that although study participants were drawn from a large, population-based sample, this sample is over-represented by white, upper middle class, college educated parents and therefore is not representative of the population at large.…”
Section: Discussionsupporting
confidence: 71%
“…Studies among caregivers of infants, school-age children, and adolescents have also shown that eating-related routines are embedded in the social and cultural context (Bauer, Hearst, Escoto, Berge, & Neumark-Sztainer, 2012; Berge et al, 2013; Datar et al, 2014; Fulkerson et al, 2011; Moore, Goodwin, Brocklehurst, Armitage, & Glenny, 2017; Trofholz et al, 2018). The present study is novel because it is one of the first to assess eating-related routines among families with preschoolers (Agrawal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%